Utilization Of CCTV As a Security System Using YOLOv8 Algorithm (Case Study Of Desty Collection Clothing Store) - Mustafian, Muhammad Rizki; Dali , Sri Wahyuni; Suharto, Nugroho (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
This study aims to prevent crimes such as theft that have occurred in the past, where a former employee committed theft by duplicating the store key. By developing a system that integrates Closed-Circuit Television (CCTV) technology with the You Only Look Once version 8 (YOLOv8) algorithm for real-time human detection. YOLOv8 was chosen for its ability to detect objects with high accuracy and speed. The system sends a signal to the ESP32 module via Firebase when detecting a human presence outside operational hours, activating a buzzer as an alarm. The security mode can be controlled via an application to activate or deactivate the alarm. When the security mode is deactivated, the buzzer will not sound even if a human is detected. The system also records CCTV screenshots upon detecting a human for monitoring and verification purposes. Implementing this system can enhance security with effectiveness, flexibility, and the potential to reduce negative incidents outside the store's operational hours. System testing results showed the ability to detect human presence at lighting levels of 1-2 Lux with an average confidence score of 63,4 percent, and at 54-56 Lux with an average confidence score of 71,6 percent.